New perspectives on Jewish-Christian relations : in honor of David Berger - Carlebach, Elisheva.; Schacter, Jacob J.; Berger, David. (The Brill Reference Library of Judaism, 2012)
The delicate balance between toleration and repulsion of the Jews, a tiny minority living within the Christian world, stands at the center of studies of religion and society. The development of this difficult relationship on many levels, theological, institutional, and individual, is a matter of continuing relevance in religious history from ancient to contemporary contexts. This volume, written by the leading scholars of Jewish-Christian engagement, seeks to revisit the question in light of new sources and re-readings of older sources. The old view of two implacable enemies battling for their version of truth, of Jews living as insular pariahs within a hostile world, the tale of persecution by the mighty of the weak, has given way to a much more nuanced understanding of areas of congruence, of cultural, economic, and social interchange. The volume examines changes in the Christian posture toward the Jews occurring in a time and place of tremendous cultural and religious creativity in Western European society. It seeks to understand how Jews integrated elements of Christian culture into their own. The volume spans some of the key turning points in the Jewish-Christian relationship and re-examines critical texts, religious disputations, and cultural interactions.